Special Issue "Selected Papers from PROPOR 2020" - Quaresma, Paulo (2022)
PROPOR 2020 will be the 14th edition of the biennial PROPOR conference, hosted alternately in Brazil and in Portugal. Past meetings were held in Lisbon, PT (1993); Curitiba, BR (1996); Porto Alegre, BR (1998); Évora, PT (1999); Atibaia, BR (2000); Faro, PT (2003); Itatiaia, BR (2006); Aveiro, PT (2008); Porto Alegre, BR (2010); Coimbra, PT (2012); São Carlos, BR (2014), Tomar, PT (2016), and Canela, BR (2018). More detailed information: https://propor.di.uevora.pt/. The authors of a number of selected full papers of high quality will be invited after the conference to submit revised and extended versions of their originally-accepted conference papers to this Special Issue of Information, published by MDPI, in open access. The selection of these best papers will be based on their ratings in the conference review process, quality of presentation during the conference, and expected impact on the research community. Each submission to this Special Issue should contain at least 50% of new material, e.g., in the form of technical extensions, more in-depth evaluations, or additional use cases and a change of title, abstract, and keywords. These extended submissions will undergo a peer-review process according to the journal’s rules of action. At least two technical committees will act as reviewers for each extended article submitted to this Special Issue; if needed, additional external reviewers will be invited to guarantee a high-quality reviewing process.